The Effects on the Electromagnetic Parameters and Performance by Magnetic Slot Wedge in a Squirrel cage Induction Motor - XIE Ying; WU Xin; LI Fei (Journal of Harbin University of Science and Technology)
Replacing the common insulation slot wedges with magnetic slot wedges in the stator slots can change the electromagnetic performance of motor, so the magnetic field, air-gap coefficient and slot leakage reactance in a squirrel cage which using common slot wedges and magnetic slot wedges were calculated accurately and compared in this paper. Based on the results of transient magnetic fields, the influences of magnetic slot wedge on surface loss、iron loss、torque、electromagnetic force and vibration were analyzed in depth. Meanwhile, the forces suffered on magnetic slot wedges were also be researched. The results show that the magnetic slot wedge can improve the distribution of air-gap flux density effectively and then reduce the losses、electromagnetic forces and vibration. But the higher relatively permeability it is, the maximum and starting torque of the motor are smaller and the forces suffered on magnetic slot wedge are greater, and the magnetic slot wedges are more easier to be damaged, so when to choose the suitable relatively permeability of magnetic slot wedge, comprehensive factors should be taken into account.